Theoretical and Experimental Study of Copper Electrodeposition in a Modified Hull Cell - Srinivas Palli; Suhash R. Dey (International Journal of Electrochemistry)
The primary current distribution and the resistance of a modified Hull cell are calculated by using conformal mapping technique coupled with numerical evaluation of the resulting integral equations. An approximate analytical expression for the primary current distribution of a modified Hull cell is presented. The primary current distribution along the cathode surface is noticed varying in controlled manner as a function of position on the substrate. The current distributions (primary, secondary, and tertiary) in the cell have also been calculated at different applied average current densities (2, 4.1, and 8.2 mA cm−2) through numerical simulation by using finite element based software. The numerical simulation result of the primary current distribution is then compared with the analytical solution and a good match is found. Experimentally, single Cu metal electrodeposition is carried out at different applied average current densities (2, 4.1, and 8.2 mA cm−2) in a modified Hull. The current distribution (primary, secondary, and tertiary) results obtained from the numerical simulation are compared with the experimental results and a satisfactory match is found. Surface morphology of the Cu deposits is examined using scanning electron microscopy (SEM).